2015
DOI: 10.1088/0004-637x/801/1/41
|View full text |Cite
|
Sign up to set email alerts
|

MOST1.6 EARTH-RADIUS PLANETS ARE NOT ROCKY

Abstract: The Kepler Mission, combined with ground based radial velocity (RV) follow-up and dynamical analyses of transit timing variations, has revolutionized the observational constraints on sub-Neptunesize planet compositions. The results of an extensive Kepler follow-up program including multiple Doppler measurements for 22 planet-hosting stars more than doubles the population of sub-Neptunesized transiting planets that have RV mass constraints. This unprecedentedly large and homogeneous sample of planets with both … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
712
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 744 publications
(768 citation statements)
references
References 39 publications
42
712
1
Order By: Relevance
“…The 10planets that we add in this study span a wide range in radii from super-Earth size to Neptune size. The wide scatter in Figure 25(a) shows a lack of rocky planets more massive than 10 M ⊕ , consistent with Rogers (2015). All the planets more massive than Neptune in Figure 25(a) are less dense than water ice and must retain deep atmospheres.…”
Section: ±54supporting
confidence: 70%
See 3 more Smart Citations
“…The 10planets that we add in this study span a wide range in radii from super-Earth size to Neptune size. The wide scatter in Figure 25(a) shows a lack of rocky planets more massive than 10 M ⊕ , consistent with Rogers (2015). All the planets more massive than Neptune in Figure 25(a) are less dense than water ice and must retain deep atmospheres.…”
Section: ±54supporting
confidence: 70%
“…We simulate planetary orbits with an eighth-order DormandPrince Runge-Kutta integrator (Fabrycky 2011;Lissauer et al 2011aLissauer et al , 2013Jontof-Hutter et al 2014, 2015 and compare simulated transit times to the observed transit times. TTVs are expressed as the difference between the observed transit time and a calculated linear fit to the transit times (O-C).…”
Section: Physical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…It is becoming clear that planets with radii larger than around 1.5 R ⊕ cannot be purely rocky (e.g. Rogers 2015), however the nature and quantity of the lighter component of planets inferred to have low density is unclear. Planets with radii of around 2-3 R ⊕ can be well fit by a rocky core with a hydrogen-helium envelope that comprises ∼0.1-5 per cent of the planet mass (e.g.…”
Section: Giant Collisions In Super-earth Systemsmentioning
confidence: 99%